APPLICATION OF TOTAL PRODUCTIVE MAINTENANCE (TPM) CONCEPT IN PALM OIL MILL FACTORY (Jurnal Mekanikal, 2018)
This study is about the application of total productive maintenance (TPM) concept in a palm oilmill factory. The objective of this paper is to highlight the advantage of TPM concept and toincrease the operating efficiency of equipment recognized as fhe overall equipment efficiency(DEE) on shop floor. n" consequence this should bring benefits to the particular factory. A casestudy was carried our in a palm oil mill factory to investigate existing situation. Pilot equipmentwas selected to serve as a target for TPM implementation in improvement prioritization analysis. In consequence, a list of all possible causes of losses was established and countermeasures to eliminate losses were recommended.
Keywords: TPM; OEE; First Pilot Equipment. Availability; Performance Rate. Quality Rale. Losses; Autonomous Maintenance.